Screening Of Phytochemicals Identified And Antioxidant Activity Of Aegiceras corniculatum Extract That Cultivates From The Mangrove Area Of Tarakan City - Imra Imra; Mohammad Fadnan Akhmadi; Diana Maulianawati; Fitri Awalia Nur; Sari Afriani (Jambura Fish Processing Journal, 2022)
Aegiceras corniculatum is mangrove vegetation that is widely spread in the mangrove area in Karang Rejo, Tarakan City and it has the potential for the development of drugs from natural ingredients from tropical sea coasts. The purpose of this study was to determine the water content, bioactive compounds, and antioxidant activity of A. corniculatum. The methods used were the analysis of water content, analysis of bioactive compounds using the phytochemical method, and analysis of antioxidant activity using the DPPH method. This study showed the percentage of moisture or water content in the leaf and fruit extracts of A. corniculatum were 1.83% and 1.95%, respectively. The bioactive compounds detected in the leaf and fruit extracts came from flavonoids, alkaloids, tannins, phenol hydroquinone, and saponins. The antioxidant analysis showed that the fruit and leaf crude extracts had an antioxidant activity with IC50 values were        129.7 ppm and 365.8 ppm, respectively.